Space Optimization for Raw Material Transportation: Reducing Environmental Impact - Taraa Chaymae; Ezzine Latifa; Dadda Afaf; Elallouli Ikram; Ayyadi Aya; Elmoussami Haj (E3S Web of Conferences)
In today’s industrial landscape, adhering to lean manufacturing principles and achieving operational excellence is increasingly vital due to rising competition. Eliminating waste, or Muda is essential for attaining a high level of lean manufacturing. One significant area for improvement is space optimization, which can be applied to production areas and logistic warehouses on a macroeconomic scale, or to trucks and pallets on a microeconomic scale. This study focuses on optimising truck space for the transportation of raw materials. An in-depth analysis of heuristics and metaheuristics methods was conducted to select the most suitable approach for this context. The chosen metaheuristic was then tailored in terms of parameters and design for this specific application. Simulation results indicate the optimal number of trucks required to meet demand and provide a 3D layout for storing raw material-filled boxes on pallets and pallets in trucks. The proposed solution is versatile and can be adapted for various storage optimization challenges within a given space.